2019
DOI: 10.25258/ijddt.v9i3.29
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, practice and pattern of self-medication among medical students in Al-Iraqia Medical College, Baghdad, Iraq

Abstract: Introduction: Self-medication is increasingly being a common practice worldwide more so amongst the medical students. This study aimed to assess the prevalence of self-medication among the medical students and to describe the self-reported practice and pattern of medication by undergraduate medical students at Al-Iraqia University in Baghdad city. Methods: This study is a cross-sectional survey. Out of 440 students enrolled, 400 (>90%) responded. The data was collected using self-administrated pretested que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
3
2
1
Order By: Relevance
“…The assessment of the sources of information used by medical students to learn about COVID-19 revealed an expected massive reliance on mass media, followed by social media, whereas few of them use the medical search engine or articles as a source of information. This is in accordance with other studies when the major source of information for medical students was TV & radio [13], and social media [10,15,20]. We also found reliable sources of information, like journals and articles, medical search engines, and webinars, are less used, even within a subpopulation that should be more familiar than the public with credible medical websites.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The assessment of the sources of information used by medical students to learn about COVID-19 revealed an expected massive reliance on mass media, followed by social media, whereas few of them use the medical search engine or articles as a source of information. This is in accordance with other studies when the major source of information for medical students was TV & radio [13], and social media [10,15,20]. We also found reliable sources of information, like journals and articles, medical search engines, and webinars, are less used, even within a subpopulation that should be more familiar than the public with credible medical websites.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are more or less similar to those of other studies [10,13,21]. Nonetheless, the usage of those information sources among Sudanese medical students is much lower than that reported in other studies [10,13,15,20]. The current study showed a significant correlation between the source of information and the level of knowledge, which agrees with other studies [15,21].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our sample was consisting of 505 medical undergraduate students. Our study shows students have 85% very good knowledge towards covid-19 which is done during early phase of lockdown (25 th march 2020 to 19 th May 2020) which is in line with other previous studies 13,14 .…”
Section: Fig 1: Knowledge Among Medical Undergraduate Students Toward...supporting
confidence: 92%
“…Nevertheless, this study finding indicates that over the period the knowledge and positive attitudes levels have increased among the adult people in Bangladesh. However, the knowledge level among the adult people in Bangladesh is comparable to Ethiopia (76%) [40], Saudi Arabia (80%), and Pakistan (80%) [41], and India (70%) [42], but lower than observed in the Philippines (92%) [43] and Iraq (92%) [44]. These differences in knowledge across the countries might be because of differences in populations and tools of examination to assess knowledge about COVID-19.…”
Section: Discussionmentioning
confidence: 93%